2007
DOI: 10.1016/j.acn.2006.09.004
|View full text |Cite
|
Sign up to set email alerts
|

The Personality Assessment Inventory in individuals with Traumatic Brain Injury

Abstract: This study examined the Personality Assessment Inventory (PAI) in 95 individuals who had suffered a traumatic brain injury (TBI). Participants were recruited from a rehabilitation hospital (n=60) and a military hospital (n=35); despite differences in demographics and injury characteristics groups did not differ on any of the clinical scales and were thus combined. In the combined group, the highest mean clinical scale elevations were on Somatic Complaints, Depression, and Borderline Features and the most commo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
17
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(19 citation statements)
references
References 21 publications
2
17
0
Order By: Relevance
“…It has shown growing applicability in clinical populations, including borderline pathology (Stein, Pinsker-Aspen, & Hilsenroth, 2007), alcohol dependency (Schinka, 1995), forensics (Edens & Ruiz, 2008), posttraumatic stress disorder (McDevitt-Murphy, Weathers, Flood, Eakin, & Benson, 2007), and individuals with head injuries (Demakis et al, 2007;Kurtz, Shealy, & Putnam, 2007). Both the MMPI and PAI are multidimensional, have sound psychometric properties, and share many commonalities in the clinical symptoms assessed, including scales tapping symptoms of depression, anxiety, somatic focus, paranoia, mania, antisocial features, and schizophrenia.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…It has shown growing applicability in clinical populations, including borderline pathology (Stein, Pinsker-Aspen, & Hilsenroth, 2007), alcohol dependency (Schinka, 1995), forensics (Edens & Ruiz, 2008), posttraumatic stress disorder (McDevitt-Murphy, Weathers, Flood, Eakin, & Benson, 2007), and individuals with head injuries (Demakis et al, 2007;Kurtz, Shealy, & Putnam, 2007). Both the MMPI and PAI are multidimensional, have sound psychometric properties, and share many commonalities in the clinical symptoms assessed, including scales tapping symptoms of depression, anxiety, somatic focus, paranoia, mania, antisocial features, and schizophrenia.…”
mentioning
confidence: 99%
“…Application of the PAI in mild and moderateto-severe head injury samples found that mild head injury participants showed elevated scores on two scales, Somatic Complaints and Depression, whereas moderateto-severe patients demonstrated higher scores on Antisocial Features and Alcohol Problems scales . Demakis et al (2007) used the PAI to provide descriptive data on elevations and common personality profiles in a sample of 113 individuals with TBI. Elevations were commonly seen on scales tapping somatic complaints, depression, borderline features, paranoia, and schizophrenia.…”
mentioning
confidence: 99%
“…Elevations on other clinical scales and in particular the Somatic Complaints (SOM) and Depression (DEP) scales, which include items such as 'difficulty with memory and concentration' and 'headaches and dizziness', may also be confounded by the typical symptoms of brain injury. Indeed, clinical elevations on these two scales with mean T-scores greater than 60 have been demonstrated in brain injury studies that have conducted PAI profile analyses [33,34]. Similarly, in a study of chronic pain patients [35], endorsement of items on the SOM and DEP scales, particularly items related to physiological manifestations of depression, was elevated relative to the normative sample.…”
Section: Introductionmentioning
confidence: 83%
“…Another study examined the PAI in 95 individuals with traumatic brain injury (Demakis et al, 2007). Factor analysis indicated a solution similar to findings from the standardization sample.…”
mentioning
confidence: 89%